Gender Differences in Stress Management: A Literature Review - Agu, Paul Chinedu; Kalu, Innocent Ndu; Ezekwe, Athony Chidi (Archives of Business Research, 2019)
Though most experts agree that a balance of gender in the workplace is ideal, studies show that women tend to excel in some areas and men excel in others. However, under the present period of economic hardship, social upheavals and political uncertainty, employees from all works of life, ages, sexes, and levels are exposed to work stress. As such, different persons adopt different strategies to cope with and manage workplace stress. This study draws from an on-going study on gender differences on coping and managing work stimulated stressors among employees. The research method adopted was a multi-methods literature search approach. New models on the causes of stress, effects of occupational stress and effects of coping and managing work stress were proposed. In spite of the identified differences that exist between men and women in the workplace, the literature reviewed in this work offered inconclusive results with regard to who among the genders manages workplace stress better than the other.